ANALISIS ANGGARAN KEUANGAN PADA DINAS PERHUBUNGAN KABUPATEN TAPANULI TENGAH - Daniel Sitorus; Ramadiah Hanum; Jeniusman Hutagalung (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
This study aims to describe the financial budget analysis at the Central Tapanuli Regency Transportation Service. A qualitative and quantitative descriptive approach is used in this study using a case study design. The data source for this study used purposive sampling, in which researchers took samples for data sources based on Sources of Funds and Users for the 2019-2021 FY and people who are considered to know best about what researchers expect. Data obtained through observation, interviews and documentation. Data analysis was carried out using the steps of data collection, data presentation, data analysis and drawing conclusions. The conclusion of this study, it was found that the financial budget analysis at the Central Tapanuli Regency Transportation Service. The Department of Transportation of Central Tapanuli Regency has a Financial Budget Analysis, namely in the form of a Budget Activity Plan starting with drafting a budget for the needs of the activities of the Central Tapanuli Regency Transportation Service. An accountability report prepared by the Central Tapanuli Regency Transportation Service regarding recipients and financial expenditures